Respon Tanaman Cabai Rawit (Capsicum fratescens L.) Tehadap Pemberian Pupuk Kandang Kambing Dan Pupuk Organik Cair Kulit Pisang Kepok - Sisinderlina, Yuyu; Raisawati, Tatik; Sari, Dia Novita; Parwito, Parwito (SINTA Journal (Science, Technology, and Agricultural), 2025)
One of the efforts to increase the production of cayenne pepper is fertilization. Fertilizers commonly used are inorganic fertilizers and organic fertilizers. The use of liquid organic fertilizer from kepok banana peel is one of the The study aims to determine the effect of a combination of goat manure and liquid organic fertilizer from kepok banana peel to increase the growth and yield of cayenne pepper plants. This study used a factorial Complete Randomized Block Design. The first factor is the dose of goat manure (K) with 3 levels, namely: K0 = 0 dose (control), K1 = 150 g plant-1 K2 = 300 gr. plant-1. The second factor is the dose of banana peel POC (P) with 3 levels, namely: P0 = 0 ml. plant-1 (Control), P1 = 30 ml plant-1, P2 = 60 ml. plant-1. The results showed that the interaction between goat manure 0 g. plant-1 with POC 60 ml. plant-1 produced the highest plant height. The interaction between goat manure 300 g.plant-1 with POC 60 ml.plant-1 produces the highest number of leaves. The dose of manure 300 g.plant-1 has an effect on the total number of fruits per plant.